Microstructure and mechanical properties of extruded Mg–Zn–Mn–Ca alloys - Sha Sha; Feng Wang; Rongguang Li; Hang Zhang; Wenyuan Cong; Boshu Liu; Shanshan Li; Yan Tang (Journal of Materials Research and Technology, 2024)
In this work, the influence of Mn and Ca doping on the microstructure and mechanical properties of Mg–3Zn, Mg–3Zn-0.5Mn, and Mg–3Zn-0.5Mn-1.2Ca alloys is systematically investigated. The addition of Mn elements is shown to exert no obvious effect on the microstructure of as-cast, as-homogenized, and extruded Mg–3Zn alloys. In contrast, the introduction of Ca into the extruded Mg–3Zn-0.5Mn alloy promotes the formation of nano-sized compounds and enhances grain refinement compared to the other two alloys. The extruded Mg–3Zn-0.5Mn alloy exhibits the higher yield strength (YS, 155 MPa) and ultimate tensile strength (UTS, 183 MPa) but the lower elongation (13%) than the extruded Mg–3Zn alloy (YS of 130 MPa, UTS of 175 MPa, and elongation of 25%). The improved strength of the extruded Mg–3Zn-0.5Mn alloy is mainly attributed to the refined grains, while both the lack of twinning deformation and strong texture result in ductility loss. The most optimal combination of strength and ductility is achieved in an extruded Mg–3Zn-0.5Mn-1.2Ca alloy (YS of 180 MPa, UTS of 250 MPa, and elongation of 26%). This suggests that fine grains and high volume fraction of nano-sized MgZn2 compounds contribute mainly to the strength of Mg–3Zn-0.5Mn-1.2Ca alloy. Although the grain refinement also facilitates the suppression of twinning in the extruded Mg–3Zn-0.5Mn-1.2Ca alloy, the weak texture and fine homogeneous grains are conducive to the high ductility.